Outcomes of Tetralogy of Fallot repair performed after three years of age - Ni Putu Veny Kartika Yantie; Mulyadi M. Djer; Najib Advan; Jusuf Rachmat (Indonesian Pediatric Society, 2016)
subject of debate, however, in general repair before 3 years of age has resulted in good myocardial performance. Late repair has led to prolonged QRS duration, ventricular dysfunction in terms of myocardial performance index (MPI) and tricuspid annular plane systolic excursion (TAPSE), as well as longer intensive care unit (ICU) stays.Objective To evaluate QRS duration, right ventricular function as measured by TAPSE, and ICU length of stay (LoS) after repair of TOF performed after three years of age.Methods This retrospective cohort study was performed in children and adults who underwent ToF repair, with a minimum follow-up of 6 months. The TAPSE and QRS duration were evaluated during follow-up and compared between children who had the operation before vs. 3 years of age or older using Mann Whitney U and Chi-square tests.Results We enrolled 52 subjects who underwent ToF repair from January 2007 to June 2013 (18 in the ≤3 years-old group and 34 in the >3 years-old group). Subjects’ age at the time of repair ranged from 7 months to 25 years, with follow-up data at 24-30 months after discharge. Abnormalities of the right ventricle and left ventricle MPI were not significantly different between the two groups. However, we observed significant differences between the ≤3 years and >3 years groups in median ICU LoS [2 (range 1-9) days vs. 1.5 (range 1-46) days, respectively; (P=0.016)] and median QRS durations [118 (range 78-140) ms vs. 136 (range 80-190) ms, respectively; (P=0.039)]. The age at the time of repair did not increase the risk of having abnormal TAPSE (RR 0.85; 95%CI 0.26 to 2.79; P=0.798).Conclusion Tetralogy of Fallot repair after 3 years of age appears to not increase ICU LoS or is associated with lower TAPSE, but it is associated with longer QRS duration. [Paediatr Indones. 2016;56:176-83.].